For \( f(x)=6 x \) and \( g(x)=x+2 \), find the following functions. a. \( (f \circ g)(x) ; b .(g \circ f)(x) ; \) c. \( (f \circ g)(2) ; \) d. \( (g \circ f)(2) \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve the given functions, let's break them down step by step. To find \( (f \circ g)(x) \), we substitute \( g(x) \) into \( f(x) \). a. \( (f \circ g)(x) = f(g(x)) = f(x + 2) = 6(x + 2) = 6x + 12 \). Next, let's find \( (g \circ f)(x) \) by substituting \( f(x) \) into \( g(x) \). b. \( (g \circ f)(x) = g(f(x)) = g(6x) = 6x + 2 \). Now, let's evaluate these compositions at \( x = 2 \). c. \( (f \circ g)(2) = 6(2 + 2) = 6 \times 4 = 24 \). d. \( (g \circ f)(2) = 6(2) + 2 = 12 + 2 = 14 \). In summary: a. \( (f \circ g)(x) = 6x + 12 \) b. \( (g \circ f)(x) = 6x + 2 \) c. \( (f \circ g)(2) = 24 \) d. \( (g \circ f)(2) = 14 \)